Job Satisfaction as a Mediator: How Leadership Style and Work Environment Shape Employee Performance - Retrin Irene Putri; Efendy Zain (Human Capital and Organizations, 2026)
This study aims to determine the role of job satisfaction as a mediating variable on the influence of leadership style and work environment on employee performance. The study population comprised employees of TCT Teknik Jakarta at the Jakarta head office. The sampling technique used was saturated sampling. Data were collected by completing a questionnaire. The data analysis method used was Partial Least Squares Structural Equation Modeling, implemented with WarpPLS 7.0. The results of the study indicate that: Leadership Style has a positive effect on Employee Performance, Work Environment has a positive effect on Employee Performance, Job Satisfaction has a positive effect on Employee Performance, Leadership Style has a positive and significant effect on Job Satisfaction, Work Environment has a positive effect on Job Satisfaction, Job Satisfaction mediates the effect of Leadership Style on Employee Performance with positive results, Job Satisfaction does not mediate the effect of Work Environment on Employee Performance with positive but insignificant results. The managerial implications of these findings are that managers need to prioritize creating a supportive work environment and adopt a leadership style that enhances employee job satisfaction.